Genetic connectivity between Caucasian and Northern Velvet Scoter Melanitta fusca populations and its importance for the long-term survival of the species in the Caucasus - Paposhvili, Nika; Morkūnas, Julius; Ninua, Levan; Beridze, Tamar; Kerdikoshvili, Niko; Dekanoidze, Davit; Murtskhvaladze, Marine; Javakhishvili, Zurab; Gavashelishvili, Alexander (Wildfowl, 2023)
Historical data suggest that the Velvet Scoter Melanitta fusca once had a widespread breeding distribution throughout the Caucasus region, but recent studies have revealed that this population has declined significantly and is now restricted to a single small breeding site at Lake Tabatskuri in Georgia. This population was considered a distinct relict group, likely isolated from the continuously distributed population across the northern forest, alpine and arctic regions of western Eurasia because of its geographic isolation. Until now, however, there was no information available about the genetic structure of the potentially isolated Caucasian population and its connectivity to the rest of the more continuously distributed northern Velvet Scoter population. Here, we analysed mitochondrial cytochrome b (hereafter cyt b) sequences and nuclear genotypes at nine microsatellite loci to evaluate: (1) genetic differentiation among the Caucasian and circumpolar populations, and (2) the genetic diversity of the local population. Our analysis revealed no significant genetic differentiation between these two populations based on both genetic markers, indicating that these two regions may represent a single panmictic population. These results are important for planning future conservation measures to maintain the Velvet Scoter population in the Caucasus.